The Effect of the RADEC (Read-Answer-Discuss-Explain-Create) Learning Model on the Reading Comprehension Skills of the Fifth Grade Elementary School Students - Nura, Syarifah Rida; Hartati, Tatat (International Conference on Elementary Education, 2022)
The problem that occurs in the process of reading comprehension is the lack of precise application of the learning model. The purpose of this study was to determine the differences in the learning outcomes of students' reading comprehension skills using the RADEC model. This study uses a quantitative approach to the pre- experimental method, one group pre-test post-test design. In this study involved 18 students who were taken by random sampling. Data collection is done by providing a test instrument. The post-test data in this study was not normal, so using the Wilcoxon test, the result was that the Asymp sig (2 tailed) value was 0.000 <0.05. The conclusion is that there is an effect of using the RADEC learning model on reading comprehension skills.